The relationship between emotion regulation skills and the impact level of the event in children victims of sexual abuse - Işık, Zerrin; Deniz, Beyaz Naz; İnanıcı, Mehmet Akif (The Bulletin of Legal Medicine, 2025)
Objective: This study was conducted to examine the relationship between the level of child sexual abuse, which is frequently encountered among childhood traumas, and the impact of sexual abuse on children, and emotion regulation skills. Methods: The relational survey model was selected for the research method. The sample of the study consisted of 50 children between the ages of 12-18 who were referred by the prosecutor’s office to the Child Monitoring Center in a selected district in Istanbul in 2023. Socio-demographic Information Form, Emotion Regulation Scale for Adolescents and Revised Child Incident Impact Scale were applied to the participants. The necessary permissions for the scales administered to the participants were obtained by the scale developers via e-mail. This study was statistically analyzed using SPSS 27 software. First, the reliability of the scales was evaluated and according to the literature, Cronbach’s alpha values above 0.60 indicate that the scale is reliable. In addition, Pearson Correlation analysis was used to assess the degree and direction of the relationship between the scales, and Multiple Linear Regression test was applied to examine the predictive power of independent variables on the dependent variable. Results: According to the results, the use of internal dysfunctional and external dysfunctional emotion regulation resources, which are sub-dimensions of the emotion regulation scale for adolescents, increases the level of the impact of the event and its sub-dimensions. The use of intrinsically functional and extrinsically functional emotion regulation decreases the level of the impact of the event and its sub-dimensions...